Reviewing the Existing Observational Tools for Assessment of Circulating Nurses' Nontechnical Skills. Issue 1 (21st January 2022) - Kalantari, Reza; Zamanian, Zahra; Jamali, Jamshid; Faghihi, Aliakbar; Hasanshahi, Mehdi; Gheysari, Somayeh
Abstract: Circulating nurses are important members of surgical teams. They need to use nontechnical skills to work safely. This study aims to review the existing observational tools for the assessment of circulating nurses' nontechnical skills. Electronic resources, including Web of Sciences, PubMed, Scopus, ProQuest, CINAHL, Embase, and Google Scholar, were searched, including studies using tools for observational assessment of nontechnical skills in surgery published up to September 2019. The search process relied on the following keywords: circulating/scout/operating room nurse, observational, assessment tools, operating room nontechnical skills, task management, teamwork, communication, situational awareness, leadership, and decision making. The data were pooled from 30 eligible studies using tools for assessment of nontechnical skills in surgeries. Eight tools were found to assess nontechnical skills for the whole surgical team or individuals, including circulating nurses. Although general behaviors for all surgical team members within the tools have been recognized, there is no specific observational tool for the assessment of circulating nurses' nontechnical skills.